2021
DOI: 10.1111/ctr.14335
|View full text |Cite
|
Sign up to set email alerts
|

Current status and further potential of lung donation after circulatory death

Abstract: Lung transplantation is the only successful treatment option for endstage lung diseases. Over the last decades, lung transplantation has steadily improved, and in parallel, indications were broadened and contraindication eased. While the demand is still increasing worldwide, a chronic organ shortage remains the primary limiting factor in lung transplantation. A concerning wait-list mortality is currently reported by the Organ Procurement and Transplantation Network (OPTN), increasing within a decade from 15% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 74 publications
(182 reference statements)
1
10
0
Order By: Relevance
“…Furthermore, no blood-circulated inflation procedures in lung procurement from a DCD donor potentially contribute to the reported favorable post-transplant outcomes of this LTx category. The survival outcome of controlled DCD LTx was better than expected and comparable to that of the standard LTx using brain-dead donor lungs in previous studies ( 22 , 23 ). We speculate that this unexpectedly satisfactory clinical outcome can be partly attributed to the DCD procurement process in which lung recruitment is performed after circulatory arrest.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, no blood-circulated inflation procedures in lung procurement from a DCD donor potentially contribute to the reported favorable post-transplant outcomes of this LTx category. The survival outcome of controlled DCD LTx was better than expected and comparable to that of the standard LTx using brain-dead donor lungs in previous studies ( 22 , 23 ). We speculate that this unexpectedly satisfactory clinical outcome can be partly attributed to the DCD procurement process in which lung recruitment is performed after circulatory arrest.…”
Section: Discussionsupporting
confidence: 70%
“…speculated that this could be a result of warm ischemia increasing pulmonary edema in the donor allograft, which could be quickly resolved with fluid balance in the ICU 18 . Many studies have reported that the survival rate of lung transplant recipients from DCD lung donors is comparable to that of DBD lung donors 4,10,17–21 . Similarly, our analysis showed no significant difference in survival between those who underwent lung transplantation from donors with DCD lungs compared to those with DBD lungs.…”
Section: Discussionmentioning
confidence: 50%
“…Compared to DBD lung recipients, recipients of DCD lungs were more likely to experience PGD3 at 72 h post‐transplant, require post‐transplant ventilation, and require post‐transplant dialysis. Most studies on PGD metrics for DCD show slightly worse trends than those for DBD in the first post‐operative hours, however, functions improve quickly 4,15–18 . Villavicencio et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations